Gaspare Tagliacozzi and early modern surgery : faces, men, and pain - Savoia, Paolo (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"This book uses the work of Bolognese physician and anatomist Gaspare Tagliacozzi to explore the social and cultural history of early modern surgery; it discusses how Italian and European surgeons' attitudes to health and beauty, and how patients' gender shaped views on the public appearance of the human body. In 1597, Gaspare Tagliacozzi published a two-volume book on reconstructive surgery of the mutilated parts of the face. Studying Tagliacozzi's surgery in context corrects widespread views about the birth of plastic surgery. Through a combination of cultural history, microhistory, historical epistemology, and gender history, this book describes the practice and practitioners considered to be at the periphery of the "Scientific Revolution." Historical themes covered include the writing of individual cases, hegemonic and subaltern forms of masculinity, concepts of the natural and the artificial, emotional communities and moral economies of pain, and the historical anthropology of the culture of beauty, the face, and its disfigurements. The book is essential reading for upper-level students, postgraduates and scholars working on the history of medicine and surgery, the history of the body, gender and cultural history. It will also appeal to those interested in the history of beauty, urban studies and the renaissance period more generally"--
Patients and cases -- Patients and practitioners : swords, books, and knives -- The culture of the face -- Health and appearance -- Grafting humans and plants -- Surgery and the moral economy of pain -- Conclusion: The place of Tagliacozzi.
OCLC-licensed vendor bibliographic record.
Keywords: Tagliacozzi, Gaspare, -- 1545-1599 -- Influence; Tagliacozzi, Gaspare, -- 1545-1599.; Face -- Surgery -- Italy -- History; Surgery, Plastic -- Europe -- History -- 16th century; Surgery, Plastic -- Social aspects -- Europe; Face -- Social aspects -- Europe; Masculinity -- Social aspects -- Europe; Pain -- Social aspects -- Europe; HISTORY / General